The causality relationship between the Budget Deficit and Inflation in Egypt during the period (1991-2021) - علياء طلعت محمود علي; جمال محمود عطية; أميرة محمد عمارة (Maǧallaẗ Al-Buḥūṯ Al-Mālīyyaẗ wa Al-Tiğāriyyaẗ, 2023)
Abstract of the study: The research aims to test the causality relationship between the budget deficit and inflation in Egypt during the period from 1991 to 2021 using Granger causality test and error correction model. The results showed a two-way relationship between budget deficit and inflation, the study recommended the need to rationalize spending Government by eliminating corruption associated with it. Trying to exploit internal and external loans in investment projects instead of using them for consumption with the aim of raising the level of domestic product and national income. Increasing direct and indirect tax revenues to reduce the budget deficit. Stabilizing the price of the pound in the long term through increasing production capacity, increasing exports. Rationalizing governmental spending by eliminating corruption related to public finance. Raising the efficiency of the tax system in mobilizing financial resources by combating the phenomenon of evasion. Key words: Budget Deficit – Inflation – Egypt.